Evaluation of carvacrol (95%) for the management of parasitic bee mites, Varroa destructor - Gunesdogdu, Mustafa; Abaci, Samet Hasan (Taylor & Francis Inc, 2025)
Beekeeping is an agricultural sector that is practiced worldwide. This sector faces many challenges. The biggest challenge is to control diseases without leaving residues of veterinary drugs in the bee products. The pest that causes the most problems for beekeepers in this sector is the mite called Varroa destructor. Natural essential oils are often used to keep this mite under control. This study found that carvacrol, a non-volatile compound in essential oils, effectively controls this mite under field conditions. In addition to its acaricidal properties, carvacrol has antifungal, anti-inflammatory, antioxidant, anticancer, and immune-modulating effects. However, its long-term impact on honey bees is not well understood. The mite control rate in colonies fed 1%, 3%, and 5% carvacrol was 2.96%, 14.49%, and 30.33%, respectively (P < 0.001). There was no statistical difference in the amounts of sealed brood and bee-covered frames in the treated colonies. Although these values are not very high, it is considered that the addition of carvacrol to the colonies' feed during the feeding period supports the other control methods used. It is recommended that researchers conduct similar studies on the non-evaporating active components of various essential oils.
Keywords: Apis mellifera; carvacrol; efficacy; feeding; Varroa mites